Digital Phase Noise Compensation for DSCM-Based Superchannel Transmission System With Quantum Dot Passive Mode-Locked Laser - Govind Vedala; Maurice O'Sullivan; Rongqing Hui (IEEE Photonics Journal)
We propose a simplified digital phase noise compensation technique for a Nyquist pulse-shaped digital subcarrier multiplexed (DSCM) coherent optical transmission system, employing an optical frequency comb based on Quantum dot passive mode-locked laser (QD-PMLL). Our results show that the impact of dominant common mode phase noise can be efficiently compensated at the receiver by digitally mixing the data sideband with the complex conjugate of the residual carrier component. This digital mixing technique resulted in better bit error rate performance compared to the conventional mth power Viterbi–Viterbi algorithm for QPSK and blind phase noise compensation for 16-quadratic-amplitude modulation formats, especially in the presence of large phase noise. To this end, exploiting the mutual coherence between the mode-locked comb lines of QD-PMLL, we numerically demonstrate its potential applicability as a transmission source for coherent optical superchannel transmission.